Specificity of the Application of the Fixed Price of the EPC-contract for the Construction of Nuclear Power Plant and Facilities Abroad - Yu. B. Ponomareva; M. M. Ishchenko (Учёт. Анализ. Аудит, 2024)
This study is devoted to approaches to pricing problems during the implementation of nuclear power plant construction projects abroad from the perspective of the nuclear industry’s aspiration to take the place of a global leader. In the course of the work, the issues of client-centricity were considered, the pros and cons of various types of pricing of EPC contracts were analyzed — at fixed, approximate, and mixed prices; the appropriate and corresponding solutions were proposed. Theoretical research methods such as analogy, classification, generalization and comparative analysis, and empirical methods such as modeling and description are used.The purpose of the study was to determine the main feature, the distinctive property of the application of a fixed price of the EPC contract for the construction of nuclear power plants outside the Russian Federation.The result of the research was the proposal of two pricing options when working with local contractors, which will be of interest to qualified specialists in the field of pricing of the nuclear industry during the construction of nuclear power plants.